EROSION III: A Multicenter RCT of OCT-Guided Reperfusion in STEMI With Early Infarct Artery Patency - Jia, Haibo; Dai, Jiannan; He, Luping; Xu, Yishuo; Shi, Yongfeng; Zhao, Lei; Sun, Zhiqi; Liu, Yin; Weng, Ziqian; Feng, Xue; Zhang, Dirui; Chen, Tao; et al. (JACC. Cardiovascular interventions, 2022)
The aim of this study was to test whether optical coherence tomographic (OCT) guidance would provide additional useful information beyond that obtained by angiography and lead to a shift in reperfusion strategy and improved clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI) with early infarct artery patency. Angiography is limited in assessing the underlying pathophysiological mechanisms of the culprit lesion. EROSION III (Optical Coherence Tomography-Guided Reperfusion in ST-Segment Elevation Myocardial Infarction With Early Infarct Artery Patency) is an open-label, prospective, multicenter, randomized, controlled study approved by the ethics committees of participating centers. Patients with STEMI who had angiographic diameter stenosis ≤ 70% and TIMI (Thrombolysis In Myocardial Infarction) flow grade 3 at presentation or after antegrade blood flow restoration were recruited and randomized to either OCT guidance or angiographic guidance. The primary efficacy endpoint was the rate of stent implantation. Among 246 randomized patients, 226 (91.9%) constituted the per protocol set (112 with OCT guidance and 114 with angiographic guidance). The median diameter stenosis was 54.0% (IQR: 48.0%-61.0%) in the OCT guidance group and 53.5% (IQR: 43.8%-64.0%) in the angiographic guidance group (P = 0.57) before randomization. Stent implantation was performed in 49 of 112 patients (43.8%) in the OCT group and 67 of 114 patients (58.8%) in the angiographic group (P = 0.024), demonstrating a 15% reduction in stent implantation with OCT guidance. In patients treated with stent implantation, OCT guidance was associated with a favorable result with lower residual angiographic diameter stenosis (8.7% ± 3.7% vs 11.8% ± 4.6% in the angiographic guidance group; P < 0.001). Two patients (1 cardiac death, 1 stable angina) met the primary safety endpoint in the OCT guidance group, as did 3 patients (3 cardiac deaths) in the angiographic guidance group (1.8% vs 2.6%; P = 0.67). Reinfarction was not observed in either group. At 1 year, the rates of predefined cardiocerebrovascular events were comparable between the groups (11.6% after OCT guidance vs 9.6% after angiographic guidance; P = 0.66). In patients with STEMI with early infarct artery patency, OCT guidance compared with angiographic guidance of reperfusion was associated with less stent implantation during primary percutaneous coronary intervention. These favorable results indicate the value of OCT imaging in optimizing the reperfusion strategy of patients with STEMI. (EROSION III: OCT- vs Angio-Based Reperfusion Strategy for STEMI; NCT03571269).